An intermediate in the phage lambda site-specific recombination reaction is revealed by phosphorothioate substitution in DNA. - Kitts, P A (1988)
It has been proposed that phage lambda site-specific recombination proceeds via two independent strand exchanges: the first exchange forming a Holliday-structure which is then converted into complete recombinant products by the second strand exchange. If this hypothesis is correct, one should be able to trap the putative Holliday intermediate by preventing the second strand exchange. In this paper, we show that substitution of phosphorothioate for phosphate in one strand of a recombination site is an effective way to block recombination while permitting the accumulation of a novel structure. This effect is seen only when phosphorothioate is positioned at a point of potential cleavage by Int recombinase, demonstrating that the inhibition of strand exchange is highly specific. Analysis of the novel structure that accumulates in these reactions proves that it contains a Holliday joint. Holliday-structures can also be detected in unblocked recombinations but are present at very low levels. The characteristics of Holliday-structure formation that we describe substantiate the proposed recombination pathway.